2018
DOI: 10.1007/s11606-018-4731-0
|View full text |Cite
|
Sign up to set email alerts
|

Physician Empathy Is Not Associated with Laboratory Outcomes in Diabetes: a Cross-sectional Study

Abstract: BACKGROUND: One widely cited study suggested a link between physician empathy and laboratory outcomes in patients with diabetes, but its findings have not been replicated. While empathy has a positive impact on patient experience, its impact on other outcomes remains unclear. OBJECTIVE: To assess associations between physician empathy and glycosylated hemoglobin (HgbA1c) as well as low-density lipoprotein (LDL) levels in patients with diabetes. DESIGN: Retrospective cross-sectional study. PARTICIPANTS: Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…To develop empathy studies relevant to inform medical education, it is crucial, at this moment, to clarify which scale—if any—offers measure which correlates with meaningful clinical or educational outcomes. For example, recently, Chaitoff et al 21 found that self-assessed empathy levels of primary care physicians were not correlated with laboratorial outcomes in patients with diabetes. This result enlightens the debate on the correlation between self-assessed empathy and clinical outcomes by showing that a relationship of cause–effect between those two variables is unlikely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To develop empathy studies relevant to inform medical education, it is crucial, at this moment, to clarify which scale—if any—offers measure which correlates with meaningful clinical or educational outcomes. For example, recently, Chaitoff et al 21 found that self-assessed empathy levels of primary care physicians were not correlated with laboratorial outcomes in patients with diabetes. This result enlightens the debate on the correlation between self-assessed empathy and clinical outcomes by showing that a relationship of cause–effect between those two variables is unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus likely that the same is the case for resident or student empathy, but this remains to be confirmed empirically. Moreover, a recent study showed a lack of correlation between self-assessed empathy by primary care physicians and clinical outcomes in patients with diabetes 21. The lack of correlation between self-assessed empathy and both patients’ assessments and clinical outcomes is a powerful argument to expand the field towards including patients’ perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 More importantly, statistically significant associations have been reported between physicians' scores on the JSE and tangible clinical outcomes in diabetic patients in the United States 16 and Italy. 17 Although researchers at the Cleveland Clinic failed to reproduce significant associations between physician empathy and patient outcomes, 18 this inability to reproduce the findings was attributed to issues related to the internal and external validity of the findings. 19 Another study 20 22 In a study at the Cleveland Clinic, 23 statistically significant associations were observed between physicians' JSE scores and standardized measures of patients' communication experiences with their physicians.…”
Section: Researchers In the United States And Abroad Havementioning
confidence: 99%
“…Research has shown that a practitioner’s ability to empathize is a trait preferred by some patients [12] and that the ability to take the perspective of patients is associated with greater patient satisfaction [13]. Further, physicians who score highly on a measure of empathy have patients with more positive clinical outcomes for diabetes [14]—however, there also exist discordant data [15]—and patient ratings of provider empathy are associated with better health outcomes, including a shorter and less severe experience with the common cold [16, 17].…”
Section: Introductionmentioning
confidence: 99%